2020
DOI: 10.1002/macp.202000192
|View full text |Cite
|
Sign up to set email alerts
|

The “Superlubricity State” of Carbonaceous Fillers on Polymer Composites

Abstract: In 2019 Ferreira et al. observed for the first time the influence of the superlubricity phenomenon of platelet‐like fillers on the properties of high molecular weight polyethylene (HMWPE) in the molten state. At the time, the study was carried out in the solid state of the polymer, analyzing the influence of the superlubricity phenomenon of oxide graphene and oxide graphite (GrO) agglomerates on the mechanical properties of the HMWPE. It was observed that the agglomerates, due to their superlubricity state, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…As can be seen, the PCU + GO-2 composites mechanical performance results from the particle microdomains presence. Ferreira et al showed that carbonaceous filler microdomains have an important role in the mechanical properties development of polymer composites because of its superlubricity effect 68 . The domains are formed by the agglomeration of small GO blocks bonded by secondary forces, and it is possible that during a high deformation regime enough tension is reached to induce the GO block slipping, as shown in Figure 13.…”
Section: Polymer Nanocomposite Characterisationmentioning
confidence: 99%
“…As can be seen, the PCU + GO-2 composites mechanical performance results from the particle microdomains presence. Ferreira et al showed that carbonaceous filler microdomains have an important role in the mechanical properties development of polymer composites because of its superlubricity effect 68 . The domains are formed by the agglomeration of small GO blocks bonded by secondary forces, and it is possible that during a high deformation regime enough tension is reached to induce the GO block slipping, as shown in Figure 13.…”
Section: Polymer Nanocomposite Characterisationmentioning
confidence: 99%
“…Ferreira et al (2019 and 2020) recently studied the mechanical tensile properties of the high-molecular-weight polyethylene (HMWPE) nanocomposite containing 0.1 wt.% of mGO and graphite oxide (GrO), and they observed that due to the high viscosity of the matrix, this nanocomposite and composite had a high content of agglomerates but with satisfactory ultimate tensile properties [ 12 ]. Their research showed that the agglomerates are included in the HMWPE matrix and are not segregated at the boundary of the powders, not weakening the material.…”
Section: Introductionmentioning
confidence: 99%
“…Another essential feature of this system is that during the processing of the HMWPE nanocomposite, the polymer flow inside the extruder guides the agglomerates in the same direction, conducting the mGO agglomerated flakes, so they are organised parallel to each other, similar to playing cards. They also reported that agglomerates arranged in this way can act as lubricants by slipping between the agglomerated flakes (superlubricity phenomenon) [ 12 , 13 ]. Slips from the agglomerates can help the polymer achieve greater tensile toughness in the solid state and reduce viscosity in the molten state as they are present in small amounts [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations